WORK-LIFE BALANCE ON THE FEMALE NURSES AT THE INPATIENT INSTALLATION OF NON-SURGICAL INTERNAL MEDICINE - Fitria Rahmi; Siti Afifi Luthfia; Lala Septiyani Sembiring (International Humanities and Applied Science Journal, 2022)
The purpose of this research is to obtain an overview of the work-life balance among the female nurses at the Inpatient Installation of Non-Surgical Internal Medicine at the Central General Hospital of DR. M. Djamil Padang. The types of sampling techniques were using the saturated sampling, as many as 74 female nurses at the Inpatient Installation of Non-Surgical Internal Medicine. The data were obtained through a measuring instrument, namely the Work-Life Balance Scale (WLBS) from Fisher, Bulger, and Smith (2009) which has been modified by Novelia (2013). The method used in this research is the descriptive quantitative. Based on the results of the analysis of the research, it was found that the majority of female nurses at the Inpatient Installation of Non-Surgical Internal Medicine at the Central General Hospital of DR. M. Djamil Padang has a high level of the work-life balance. This means that the female nurses have been able to work and to develop the role that they live by being able to manage the time between working and personal life with their best ability to regulate personal life so as not to interfere with the work they do.